Dexmedetomidine as an anaesthetic adjunct for management of difficult airway in a patient with facial injury following bear maul - Parajuli, Bashu Dev; Udaya, Rejin Kumar; Sharma, Anubhav; Shrestha, Gentle Sunder (Journal of Society of Anesthesiologists of Nepal, 2015)
The management of difficult airway is one of the most challenging tasks for the anaesthesiologist. Life threatening cannot intubate and cannot ventilate situation can be avoided by performing awake-fibreoptic intubation. Although there are many techniques described for fibreoptic intubation but relative merits and demerits of each technique should be considered. The key to successful awakefibreoptic intubation depends upon the meticulous preparation of the patient and the equipments. Many methods of sedation have been described but theirs side effects are the limitations. Dexmedetomidine, a selective alpha2 adrenergic agonist, has unique property of conscious sedation. Besides, dexmedetomidine has additional property of analgesia, reflex blunting and anti-sialogogue, which can further improve the success rate of awake-fibreoptic intubation in cases with difficult airway. We described a case of bear maul of face with anticipated difficult airway successfully conducted awake-fibreoptic intubation with the use of dexmedetomidine. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 77-79